2001
DOI: 10.1046/j.1464-410x.2001.02028.x
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblasts defined by electron microscopy suggest the dedifferentiation of smooth muscle within the sac walls associated with congenital inguinal hernia

Abstract: Objective To ascertain the presence of myofibroblasts in sacs associated with inguinal hernia in children, through an ultrastructural evaluation using electron microscopy Materials and methods Sacs were obtained from 10 boys and 10 girls (of similar age, ≈ 45 months) with inguinal hernia and processed for electron microscopy. Thin sections were examined specifically for the presence of myofibroblasts. Results The ultrastructural evaluation showed myofibroblasts with classical electron microscopic features wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
11

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 11 publications
2
23
0
11
Order By: Relevance
“…Tanyel et al [7], [8] showed that childhood inguinal hernia is related to smooth muscle within the wall of the sac. The smooth muscle bundles may have an important role both in prevention of obliteration and clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Tanyel et al [7], [8] showed that childhood inguinal hernia is related to smooth muscle within the wall of the sac. The smooth muscle bundles may have an important role both in prevention of obliteration and clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…While the sacs presenting smooth muscle have invariably disclosed myofibroblasts, some sacs have only included myofibroblasts without any additional smooth muscle [4]. Therefore, the apoptosis of smooth muscle in PV has been suggested to be a continuous process, which also involves the dedifferentiation into myofibroblasts [5]. The close correlation among the amounts of presenting smooth muscle and myofibroblasts [4], and the possibility of failed obliteration even in the presence of only myofibroblasts suggest interactions during the process.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that incomplete obliteration of PV contains a layer composed of smooth muscle and myofibroblasts that is not encountered in obliterated PV [3][4][5]. Since smooth muscle develops within the gubernaculum around the PV and it is not found in obliterated PV, it should present temporarily during a time period compatible with the descent of testis.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…While the failed descent has been proposed to reflect a failure of propulsion [2], the persistence of smooth muscle after descent has been suggested to hinder the obliteration and give rise to either inguinal hernia or hydrocele, depending upon the amount of smooth muscle [3][4][5].…”
Section: Introductionmentioning
confidence: 99%